2016
DOI: 10.1136/bmjopen-2016-013205
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the 2011 Fukushima nuclear accident on emergency medical service times in Soma District, Japan: a retrospective observational study

Abstract: ObjectiveTo assess the influence of the 3.11 triple disaster (earthquake, tsunami and nuclear accident) on the emergency medical service (EMS) system in Fukushima.MethodsTotal EMS time (from EMS call to arrival at a hospital) was assessed in the EMS system of Soma district, located 10–40 km north of the nuclear plant, from 11 March to 31 December 2011. We defined the affected period as when total EMS time was significantly extended after the disasters compared with the historical control data from 1 January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…As for the other two EMS time segments, on-scene time increased after the disaster while response time did not. Response time did not significantly change between the two periods, which was consistent with previous research immediately after the disaster 20. These results indicated that the initial performance of EMS did not change even after the disaster.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As for the other two EMS time segments, on-scene time increased after the disaster while response time did not. Response time did not significantly change between the two periods, which was consistent with previous research immediately after the disaster 20. These results indicated that the initial performance of EMS did not change even after the disaster.…”
Section: Discussionsupporting
confidence: 90%
“…A local EMS governed by the Regional Fire Department in each medical zone is thus the sole public system to provide emergency transport for patients 19. When there are a limited number of nearby emergency hospitals available, particularly in remote areas, municipalities largely depend on EMS to transport emergency patients, as reported in the previous study 20. Thus, examining the EMS time of Kawauchi Village across the disaster is useful to assess the impact of the abrupt closure of emergency hospitals nearby on emergency care access in rural areas and consider countermeasures for such extrinsic factors.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, we suggested that the primary cause of delays in EMS activities was the fact that the overall EMS was not operating normally. The triple disaster that occurred in Fukushima, Japan, in 2011 (an earthquake, tsunami, and nuclear power plant incident) caused delays in EMS transport times that lasted several months [ 12 ] ; this research showed that infectious disease outbreaks could also affect EMS transport times over several months.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 , 25 ] Health care systems in the affected areas remain heavily affected since many hospitals in the area were forced to close and remain closed even after the evacuation orders were lifted. [ 23 ] Notably, the situations of emergency transport in the area where the evacuation order was lifted have been shown to be different from those before the disaster, leading to the delay in EMS time. [ 23 , 24 , 26 , 27 ] Thus, in developing effective countermeasures for nuclear disaster recovery, it is important to accumulate evidence on the medical demand and the state of emergency transport in the area where the evacuation orders were lifted.…”
Section: Introductionmentioning
confidence: 99%